Gender education and equality in a global context : conceptual frameworks and policy perspectives - Fennell, Shailaja, 1964-; Arnot, Madeleine (Routledge, 2008)
Focusing on gender equality by exploring the interrelations between gender, education and poverty, this work demonstrates a range of methodological frameworks for analysing gender and education with a development context.